Flirting with the Law: Queer Culture beyond Transgression? - Ivanchikova, Alla (Academic Quarter | Akademisk kvarter, 2011)
With Kirk’s argument, we also see that aesthetic practices become part of the cultural practices where transgression plays a part. One example of this combination of cultural and aesthetic practices is found in lesbian cinema, discussed in Alla Ivanchikova’s article Flirting with the Law, where Ivanchikova investigates notions of law outside the heteronormative, where the viewer is invited to flirt with the law and the law is no longer regarded as heteronormative.